1987
DOI: 10.1080/01688638708405352
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an attention-training program

Abstract: Attention Process Training (APT), a hierarchical, multilevel treatment program, was designed to remediate attention deficits in brain-injured persons. The program incorporates current theories in the experimental attention literature. Four brain-injured subjects, varying widely in both etiology of injury and time post onset, underwent intensive cognitive remediation including 5 to 10 weeks of specific attention training. Results are displayed using a single subject multiple baseline across behaviors design. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
261
1
23

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(299 citation statements)
references
References 10 publications
3
261
1
23
Order By: Relevance
“…The rationale for most of the reported interventions is to restore basic attention capabilities through practice of specific components of attention, e.g., training of vigilance as well as sustained, divided and shifting attention [3,13,15]. The computerized training method used in this pilot study differs from previous studies on cognitive rehabilitation after stroke, in that it is specifically focused on WM training and does not include training of other cognitive functions.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The rationale for most of the reported interventions is to restore basic attention capabilities through practice of specific components of attention, e.g., training of vigilance as well as sustained, divided and shifting attention [3,13,15]. The computerized training method used in this pilot study differs from previous studies on cognitive rehabilitation after stroke, in that it is specifically focused on WM training and does not include training of other cognitive functions.…”
Section: Introductionmentioning
confidence: 74%
“…Several studies investigated the effectiveness of attention training in the chronic stage (>1 year) after brain injury in adults [15][16][17][18][19][20][21][22]. For a review see Cicerone et al [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…We also searched Science Citation Index for articles that referred to several well-known rehabilitation studies (Ben-Yishay et al, 1979a;Gray & Robertson, 1989;Gray, Robertson, Pentland, & Anderson, 1992;Sohlberg & Mateer, 1987). The reference section of each retrieved study was also inspected to identify additional articles.…”
Section: Sample Of Studiesmentioning
confidence: 99%
“…Most controlled studies compared attention training with an alternative treatment, without including a no-treatment condition; a very important distinction is between studies conducted in the acute and postacute stage. Cicerone et al (2000) concluded that evidence from two class I (Niemann et al, 1990;Gray et al, 1992) studies with a total of 57 subjects and two class II studies (Sohlberg & Mateer, 1987;Strache 1987) with a total of 49 subjects supports the effectiveness of attention training beyond the effects of non-specific cognitive stimulation for subjects with TBI or stroke during the post-acute phase of recovery and rehabilitation. Cicerone et al (2000) recommended such a form of intervention as a practice guideline for these persons.…”
Section: Recommendationmentioning
confidence: 99%
“…Thirteen studies were reviewed by Cicerone et al (2000), including three class I prospective RCTs (Niemann et al, 1990;Gray et al, 1992;Novack et al, 1996), four class II controlled studies (Sohlberg & Mateer, 1987, Strache, 1987Ponsford and Kinsella, 1988;Sturm and Wilmes, 1991); and six Class III studies (Wood, 1986;Ethier et al, 1989;Gray and Robertson, 1989;Gansler and McCaffrey, 1991;Wilson and Robertson, 1992;Sturm et al, 1997). Most controlled studies compared attention training with an alternative treatment, without including a no-treatment condition; a very important distinction is between studies conducted in the acute and postacute stage.…”
Section: Recommendationmentioning
confidence: 99%